Early years (Springfield, Mo Flower Pentecosal Heritage Center, 2001)
"collection of oral history interviews focuses on the early years of the Assemblies of God and Pentecostal movement."
Heritage Digital Oral Histories
Compatible with Windows 95,98,2000,ME,NT, and Macintosh computers
Keywords: Assemblies of God -- History -- Oral histories; Pentecostalism -- History -- Oral histories